P‐76: Effect of a‐IGZO Thickness Variation on Device Uniformity and Drain Currents for Dual and Single Gate Driving TFTs. Issue 1 (2nd June 2017) - Billah, Mohammad Masum; Hasan, Md Mehedi; Jeong, Duk Young; Um, Jae Gwang; Jang, Jin
Abstract : We studied the effect of a‐IGZO thickness (tIGZO ) on device uniformity and drain current (ID ) of a‐IGZO thin‐film‐transistors (TFTs) driven by the single gate (SG) and dual‐gate driving (DG‐driving). Numerical simulation using fitting density‐of‐states (DOS) exhibits 5 times larger ID and excellent uniformity with DG‐driving TFTs for a‐IGZO tIGZO <20 nm than SG‐TFT and enables the opportunity of high yield backplanes using DG‐TFTs for next generation high‐performance display applications.